Climate change mitigation in crop production developing yellow corn (Zea mays L.) varieties for salinity tolerance - Santos, Primitivo Jose A.; Descalsota, Jonathan C.; Ladia, Villamor A. (2011)
Problems due to soil salinity are widely spread throughout different agro-ecological zones. Corn (Zea mays L.) as one of the major cereal crops in the world, is adversely affected by this stress. Efforts to develop tolerant varieties are underway to limit the ill effect of salinity on corn production. Greenhouse experiments and field trials were conducted to evaluate the potential of 2 yellow corn populations or open pollinated varieties (OPVs) developed by the Institute of Plant Breeding (IPB) for salinity tolerance. Initial screenings were conducted in the greenhouse using the nutrient solutions culture with varying degree of salinity. Treatments were replicated three times and were arranged in randomized complete block design with salinity levels serving as main plot and variety as the sub-plot. Results of agronomic parameters like percent survival root and shoot length, root and shoot biomass, chlorophyll content (SPAD value) and leaf area revealed three varieties with good potential for improving their saline tolerance; these were Phil 1-115, IPB Composite 3 and IPB Composite 5. These OPVs were further evaluated by growing them under actual saline soil. IPB Composite 3 being the better of the two. Thus, IPB Composite 3 had been chosen as the best OPV candidate for yellow corn population improvement for salinity tolerance.
Keywords: Corn breeding; Crop productions; Soil salinity; Climate change